Overexpression of galectin-1 is associated with poor prognosis in human hepatocellular carcinoma following resection - Wu, Han; Chen, Pei; Liao, Rui; Li, Yi-Wei; Yi, Yong; Wang, Jia-Xing; Sun, Tai-Wei; Zhou, Jian; Shi, Ying-Hong; Yang, Xin-Rong; Jin, Jian-Jun; Cheng, Yun-Feng; et al. (Journal of gastroenterology and hepatology, 2012)
Background and Aim:  The high expression of the galectin‐1 predicts poor patient outcome in several tumors. The aim of this study was to investigate its prognostic value in patients with hepatocellular carcinoma (HCC) after resection. Methods:  Galectin‐1 and tumor‐infiltrating FoxP3+ regulatory T cells (Tregs) were validated by tissue microarrays from HCC patients (n = 386) and statistically assessed for correlations with the clinical profiles and the prognosis of the patients. Results:  We found that galectin‐1, which was prevalently upregulated in HCC, was significantly associated with tumor invasive characteristics (such as vascular invasion, incomplete encapsulation, poor differentiation, multiple number, and large tumor size). Patients with high galectin‐1 expression had a significantly poorer tumor recurrence (P = 0.025) and overall survival (P = 0.021) than those with low galectin‐1 expression. Even in early‐stage disease, high galectin‐1 expression was also independently associated with shortened survival (P < 0.001) and increased tumor recurrence (P = 0.005). Multivariate Cox proportional hazards analysis showed that galectin‐1 was an independent marker for predicting the poor prognosis of HCC. The galectin‐1 level was positively related to the number of tumor‐infiltrating FoxP3+ Tregs (r = 0.416, P < 0.001), and their combination served as a better prognosticator. The postoperative tumor recurrence and survival of HCC patients with galectin‐1high and FoxP3high were significantly poorer than the other groups (both P < 0.001). Conclusions:  Galectin‐1 might be a new prognostic factor for HCC after resection and could potentially be a high‐priority therapeutic target.